Influence of 6-Benzylaminopurine, Chitosan and Carboxy Methyl Cellulose on Quality and Shelf Life of Fresh Cut Carrot (Daucus carota L.) Shreds under Refrigerated Storage - Mandal, Debashis; Ngohla, Veronica V.; Hazarika, Tridip Kumar; Shukla, Amritesh Chandra (International Journal of Bio-resource and Stress Management, 2023)
Carrots are very popular root vegetable, highly preferred for its richness in antioxidant, vitamin-A and dietary fibre. Fresh cut carrots have gained popularity in recent time to cope with the need of ready to use fresh vegetable demand of urban cities and super markets. But storage of fresh cut carrots are difficult task as it loses moisture rapidly and become shrivelled and thus become susceptible to post-harvest decay which causes short shelf life. Present study was undertaken to evaluate the influence of 6-Benzylaminopurine (6-BAP), Chitosan and Carboxy Methyl Cellulose (CMC) on quality and shelf life of fresh cut carrot shreds under refrigerated condition. Eight post-harvest treatments viz. fruit dipping in 6-BAP at 100 ppm, 200 ppm, 300 ppm; fruit dipping in Chitosan at 1%, 2% and in Chitosan 1% along with CMC 2%, Chitosan 2% along with CMC 2% and control (treated with water) with six replications were used and statistical analysis was done by following complete randomized design. The results of the research showed that carrot shreds bilayer coated with chitosan 2% and carboxy methyl cellulose 2% had minimum percentage of physiological weight loss (8.56%) with high TSS:acid ratio (26.97), ascorbic acid (6.12 mg 100 g-1) and carotene (7.25 mg g-1) content at 15 DAS. Moreover, there was no decay in stored carrot shreds and showed maximum shelf life (25.25 days) under this treatment. However, carrot shreds bilayer coated with chitosan 1% and CMC 2% also had high shelf life (21.25 days).